2022
DOI: 10.3389/fevo.2022.868033
|View full text |Cite
|
Sign up to set email alerts
|

Paleoecological Studies at the Ancient Maya Center of Yaxnohcah Using Analyses of Pollen, Environmental DNA, and Plant Macroremains

Abstract: Yaxnohcah was a major city of the ancient Maya world, especially during the Preclassic period (1000 BCE–200 CE). Data from excavations provide important insights into the interactions between the ancient inhabitants and its surrounding Neotropical forests, a topic that, as a whole, remains largely enigmatic. This study aspired to fill that void in understanding by using traditional paleoethnobotanical approaches and a powerful new technology, the analysis of environmental DNA. Our results enabled us to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the case of the seasonal wetlands, the Cobweb Swamp records in Belize were developed in areas inside artificial channels developed by the Maya (Jones, 1994), which are dry today, while the records at Akab Muclil and Cob are wetlands in flood plains (Kylander et al, 2012;Pohl et al, 1996). A similar case happens in records obtained from sediments deposited in artificial reservoirs for keeping water (chultunes) in Aguada Mucal and adjacent reservoirs (Lentz et al, 2022). In addition, records at El Infierno (Castanet et al, 2022), El Laberinto and El Ramonal adjacent to Calakmul were developed from sediments (colluvium) deposited in seasonal swamps (Gunn et al, 2002).…”
Section: Types Of Palaeoclimatic Records In the Mamentioning
confidence: 79%
“…In the case of the seasonal wetlands, the Cobweb Swamp records in Belize were developed in areas inside artificial channels developed by the Maya (Jones, 1994), which are dry today, while the records at Akab Muclil and Cob are wetlands in flood plains (Kylander et al, 2012;Pohl et al, 1996). A similar case happens in records obtained from sediments deposited in artificial reservoirs for keeping water (chultunes) in Aguada Mucal and adjacent reservoirs (Lentz et al, 2022). In addition, records at El Infierno (Castanet et al, 2022), El Laberinto and El Ramonal adjacent to Calakmul were developed from sediments (colluvium) deposited in seasonal swamps (Gunn et al, 2002).…”
Section: Types Of Palaeoclimatic Records In the Mamentioning
confidence: 79%
“…However, the connection of modern composition with Maya times comes from the archaeological record. Identifications of pollen, charcoal, and eDNA recovered from excavations at Yaxnohcah show some dominant species present in the modern forest, such as Brosimum and Manilkara as well as Pinus that is not there today [46]. Supported by the identification of archaeobotanical remains, it is confirmed that the forest composition in ancient Maya times around Yaxnohcah had similarities to that of the present-day, though, as noted in the introduction, acknowledging that the long Maya occupation itself changed the nature of the landscape and forest.…”
Section: Discussionmentioning
confidence: 99%
“…Cyperaceae (sedge) and other aquatic plants have been identified in sediment cores from Maya reservoirs (e.g., ref. 60 ).…”
Section: Ancient Maya Reservoirs As Cwsmentioning
confidence: 99%